A Broken Heart Coexisting with Obstructive Coronary Artery Disease: Double Trouble - Juzar, Dafsah Arifa; Putra, Bayushi Eka (Jurnal Kardiologi Indonesia, 2025)
In “A Broken Heart Coexisting with Obstructive Coronary Artery Disease: Double Trouble” (Indonesian Journal of Cardiology, 43(4), 168-73. https://doi.org/10.30701/ijc.1368), there is an error noted. An error has been found in the PDF version of this article. The DOI printed in the PDF is incorrect. The correct DOI is https://doi.org/10.30701/ijc.1368. The error occurs only in the PDF; the DOI listed in the article metadata is already correct.The publisher apologizes for any inconvenience caused by this error.